Comparison of perspective passing performance in football games for persipura u-16 players pro academy elite league - Pahala Tua Hutajulu; Vega Soniawan; Muh. Ali Akbar; Ewendi Mangolo (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2022)
Technical performance studies in professional football players need to be carried out intensely. The performance data from junior elite football was very useful for talent identification and further development. However, typical research is still rarely carried out, while previous research has focused on identifying talented players based on anthropometric, physiological, psychological, sociological and technical skills data. In this study, the assessment was no longer carried out from isolated situations but shifts to special assessments in real match situations, so that the results may contribute to talent identification. The purpose of this study was to assess the passing performance of elite junior football players in actual matches by comparing the performance of the Persipura U16 team in 2018 and 2019. The average value of passing, successful passing, and accuracy of passing in the 2018 season was 157, 101, and 66%, while the average value in the 2019 season was 167, 111, and 67%, respectively. Although the value increased slightly, however based on the calculation results there were no significant differences in the passing performance of the Persipura U-16 team in 2018 and 2019 league sessions. The results provide a recommendation that the practice session of passing techniques for junior football players, particularly Persipura U-16, should be carried out more in game situations and not in isolated situations.